A proposed module in the concept culture for grade six - Madriñan, Corazon M. 1947- (1977)
The purpose of the study was to provide an instructional module on the concept of Culture for grade six. The Scope and Sequence of the UP-NSDB Project was the basis of the researcher in the selection of major concept, sub-concept and generalization. A task analysis was likewise prepared to guide the researcher in the necessary steps in preparing the module. The entire module has the following contents: notes to the teacher, notes to the students, rationale, pre-test, objectives, learning activites, post-test, and key to answers.